Plant-bee interactions and pollen flux in restored areas of Atlantic Forest - Pfeiffer, Paula Maria Montoya (2018)
The conservation and restoration of pollinators is essential for sustaining viable plant populations in fragmented landscapes because they promote genetic diversity among isolated individuals. As it is expected that populations in remnant and restored forests perpetuate with the passing of the years, restoration programs on highly fragmented agricultural landscapes should be planned with consideration for achieving this purpose. In this work, we evaluated plant-pollinator interactions in restored tropical forests, aiming to establish first, the pollination requirements of plant species in these communities, and secondly, if the pollinator requirements are being fulfilled and the interactions between plants and pollinators are being recovered throughout restoration practices. This work comprises two chapters: On the first one (\"Are the assemblages of tree pollination modes being recovered by tropical forest restoration?\") we did an extensive literature review about the pollination biology of tree species in primary forests, restoration plantings and naturally regenerated forests, to compare and identify patterns on the functional diversity and the assemblages of plant pollination modes. On the second chapter (\"Functional responses and effects from bee communities in restored tropical forests\") we sampled bees (i.e. the most important pollinators) and identified the pollen grains attached to their bodies in primary forests, restoration plantings, disturbed herbaceous areas and sugar cane fields; afterwards we analyzed and compared the functional diversity of bee communities and their floral resources, and the structure of plant-bee interactions, as well as in response to habitat isolation. We found that different restoration practices leaded to changes on patterns of abundance and species proportions of several plant pollination modes, which were stronger in locations under active restoration activities than in naturally regenerated forests. Specifically in the case of bees, we found that the demand for their function as pollinators in restoration plantings was even higher than that in primary forests, since many bee pollinated tree species were being widely and preferably used due to their great colonizing ability, or because of the many other ecosystem functions and services that they provide. We observed that bee communities were getting benefited by such over-representation of bee floral resources, since many species visited more frequently the tree species in restoration plantings than any other habitat. In spite of such preference, the bee abundance and functional diversity of bee communities was not fully recovered in restoration areas, maybe because of other habitat requirements that still remained undersupplied (e.g. nesting resources). Although the functional diversity on bee communities was high in general, only a small part, which was also the most vulnerable (i.e. larger bees that nest above-ground, have different levels of sociality and are polylectics), was the principal in charge of the pollination of the most important plant species in primary and restored forests (i.e. native woody plants, from initial successional stages and with different pollination modes). Throughout this work we analyzed and discussed the implications of these results for the recovery of plant-pollinator interactions and on future decisions in restoration and conservation planning